Analisis Faktor Risiko Kejadian Status Gizi Kurang Anak Balita Di Wilayah Kerja Puskesmas Amondo Kecamatan Palangga Selatan Kabupaten Konawe Selatan Tahun 2025 - Rahmawati; Samsudi; Rasma (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Data on malnutrition in toddlers at the Amondo Health Center in 2023 were 47 toddlers, then in 2024 from early January to November, malnutrition data increased by 64 toddlers. This study aims to determine the Risk Factors for Malnutrition in Toddlers in the Working Area of ​​the Amondo Health Center, South Palangga District, South Konawe Regency in 2025. The design of this study is quantitative with a cross-sectional approach. The population of this study was all toddlers registered in the working area of ​​the Amondo Health Center, South Palangga District, South Konawe Regency in 2024 with a total of 966 people. The sampling used was Accidental Sampling. To obtain a representative sample, the selection of subjects from each stratum or certain region was determined in a balanced or comparable manner in each matched region. The sample size used was 91 respondents. The data were analyzed using the SPSS application with the Odds Ratio test. The OR test results obtained knowledge values ​​(OR = 1.08), eating habits (OR = 0.70), family income (OR = 1.10), carbohydrate intake (OR = 2.47), protein intake (OR = 0.91) and fat intake (OR = 1.30). The conclusion that maternal knowledge, children's eating habits, family income, and nutrient intake (carbohydrates, proteins and fats) in the past are risk factors for malnutrition. It is recommended that health workers always provide information about malnutrition to the community, carry out vegetable planting movements in the community, do not carelessly give food to toddlers, always consume and provide nutritious food for the family